The Effect Of Human Resource Empowerment On Employee Performance At The Office Of The Personnel And Development Agency Human Resources Binjai City - Irma Lestari Silaban; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2024)
This study was a quantitative associative causal research aimed at analyzing the relationship between variables and determining the effect of two independent variables (exogenous) on the dependent variable. The study was conducted at the Regional Civil Service and Human Resource Development Office of Binjai City, with a population of 100 employees. The sampling technique used was saturated sampling, where all members of the population were included as samples. The data used were obtained from questionnaires distributed to respondents, consisting of employees from all divisions. The results showed that Human Resource Development (HRD) had a positive and significant effect on Employee Performance. This was evidenced by the t-count value of 15.078 > t-table value of 1.66980, with a significance value of 0.000 < 0.05. The regression coefficient of 1.334 indicated that each increase of 1 point in HRD would lead to an increase of 1.334 points in Employee Performance, assuming other variables remained constant. In addition, the coefficient of determination test showed an Adjusted R Square value of 0.790 or 79.00%, indicating that HRD had a very high influence on Employee Performance, with 21.00% of the remaining variance being influenced by factors not studied in this research. Overall, the findings of this study identified that improving Human Resource Development could contribute to the enhancement of Employee Performance at the Regional Civil Service and Human Resource Development Office of Binjai City.